Implementation of digital technologies in the educational and consulting activities of the institute of energy, automation, and energy saving to ensure academic integrity - Opryshko, O.; Shvorov, S.; Sinyavsky, O.; Makarevych, S.; Shelimanova, O.; Landyk, O.; Bondarchuk , I. (Energy and Automation, 2025)
The article examines the peculiarities of implementing digital technologies in the educational process and consulting activities using the example of the Institute of Energy, Automation, and Energy Saving in the context of modern challenges, particularly wartime conditions and a shortage of specialists in the energy sector. The methods of adapting the educational process to the needs of students who combine studying with work at critical infrastructure enterprises are described. The study explores the issue of ensuring academic integrity in the conditions of distance learning and conducting assessment activities. The risks associated with the unauthorized use of information resources, the application of artificial intelligence for generating responses, and the challenges of student identification during online exams are identified. Global experience in maintaining academic integrity and effective assessment methods, such as step-by-step monitoring, individualized assignments, and video recording of responses, are analyzed. The article also considers the impact of power outages on the educational process and ways to overcome these challenges, including the use of alternative communication methods, video conferencing services, video hosting platforms (YouTube), and corporate e-learning platforms (elearn.nubip.edu.ua). Integrated approaches to organizing the learning process are proposed, ensuring close interaction between the university and enterprises through dual education. This not only improves students’ knowledge levels but also facilitates their adaptation to real working conditions. It is concluded that the combination of digital technologies and flexible learning strategies ensures the quality of education and academic integrity even in crisis situations. The use of e-learning platforms, individualized assignments, video control, and industry integration enhances the effectiveness of the educational process and strengthens the interaction between universities and employers. Key words: digital technologies, distance learning, academic integrity, dual education